2019
DOI: 10.1007/s12630-019-01307-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transfusion outcomes in pediatric complex cranial vault reconstruction: a multicentre observational study from the Pediatric Craniofacial Collaborative Group

Abstract: Purpose Pediatric patients undergoing complex cranial vault reconstruction (CCVR) are at risk of significant perioperative blood loss requiring blood product transfusion. Minimizing allogeneic blood product transfusion is an important goal because of the associated risks and cost. The impact of patient and surgical variables on transfusion is unknown in this population. Our primary aim was to examine relationships between demographic and perioperative variables and blood product transfusion outcomes in CCVR. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“… 29 32 There have yet to be detailed reports of management for complex craniofacial children, beginning with preoperative assessment and optimization to anesthesia, intraoperative management, and intensive care recovery. 22 , 23 As cranial vault remodeling can be associated with significant morbidity and a prolonged length of stay, analyzing surgical techniques and approaches is critical to improving and optimizing recovery. In this study, we chose to analyze only children undergoing FOA, as this complex surgical approach has been associated with a historically high rate of transfusion requirement and hospital length of stay, even within cranial vault remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 32 There have yet to be detailed reports of management for complex craniofacial children, beginning with preoperative assessment and optimization to anesthesia, intraoperative management, and intensive care recovery. 22 , 23 As cranial vault remodeling can be associated with significant morbidity and a prolonged length of stay, analyzing surgical techniques and approaches is critical to improving and optimizing recovery. In this study, we chose to analyze only children undergoing FOA, as this complex surgical approach has been associated with a historically high rate of transfusion requirement and hospital length of stay, even within cranial vault remodeling.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 There has yet to be a detailed report of management for complex craniofacial children from an anesthesia or intensive care perspective. 22 , 23 Additionally, most postoperative protocols rely on direct patient examination by a provider that may only occur at certain time points, such as morning rounds, which can delay decision-making and the advancement of a child’s recovery. However, protocols and order sets that allow for decisions to be increasingly made by the bedside nursing team can allow for expedited changes based on the child’s evolving recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In an observational study examining transfusion practice in children older than 28 days who underwent surgery in different hospitals was found that younger age (29 days to 2 years) among other factors was a preoperative variable associated with increased odds of having an intraoperative or postoperative RBC transfusion [ 7 ]. A recently published register study in pediatric patients undergoing complex cranial vault reconstruction identified that age less than 24 months as one of the factors for increased RBC transfusion [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Children undergoing surgical correction of craniosynostosis often experience high rates of bleeding and blood product transfusion, increasing the risk of postoperative complications including mortality. [3][4][5] The most severe and most common perioperative issues relate to the rate and extent of blood loss, which can be up to several times the patient's total blood volume. 3,6,7 Contributing to high blood loss rates are the large surgical surfaces exposed, hyperfibrinolysis, and dilutional coagulopathy.…”
Section: Introductionmentioning
confidence: 99%
“…10,16 TXA has been shown to be effective in limiting blood loss in infants and children undergoing CCVR, and two recent retrospective reviews suggest a benefit of EACA in this population as well. 5,14,[17][18][19] While the use of EACA and TXA to limit surgically-induced hemorrhage and transfusion requirements during CCVR has been extensively studied, the comparison of EACA vs TXA in children undergoing CCVR has not yet been evaluated. The aim of this study was to compare perioperative blood loss and need for transfusion in children receiving EACA and TXA.…”
Section: Introductionmentioning
confidence: 99%